PERAN RUTGERS WPF DALAM MENANGANI KEKERASAN TERHADAP PEREMPUAN DI INDONESIA MELALUI PROGRAM “PREVENTION+” TAHUN 2016-2020 - Putri, Nachadika Shania Maera; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Cases of violence against women in Indonesia tend to increase every year, despite various efforts from the government. For this reason, Rutgers World Population Foundation (WPF) is taking part in addressing the issue of violence against women in Indonesia through the Prevention+ Program implemented in Jakarta, Lampung, Yogyakarta, and Solo by embracing women and involving men as agents of change. This research uses qualitative methods and data collection techniques from literature studies originating from books, journals, official reports, news articles, and official publications relating to the topic discussed. The pluralism perspective and theory of Non-Governmental Organizations (NGOs) put forward by Nazneen Kanji and David Lewis are used to analyze the role of Rutgers WPF in the Prevention+ Program in Indonesia, with three role classification indicators, namely as implementer, catalyst, and partner. The results of this study indicate that through the Prevention+ Program, Rutgers WPF has fulfilled the three indicators of the role of NGOs proposed by Nazneen Kanji and David Lewis. This role has had positive influence on the progress of handling violence against women in Indonesia, despite facing several challenges in its implementation. Keywords: Rutgers WPF, roles, Non-Governmental Organizations, Violence against Women, Agent of Change, Indonesia.